Electron-Phonon Renormalization in the Proton-Conducting Electrolyte BaZrO_{3} and Its Implications for High-Temperature Electrolysis - Shenli Zhang; Andrew J.E. Rowberg; Tadashi Ogitsu; Tuan Anh Pham; Joel B. Varley (PRX Energy)
Electrical leakage is an inherent problem in solid-oxide fuel and electrolyzer cells, limiting their energy-conversion efficiency. High concentrations of electrons or holes can exacerbate this issue. However, it is largely unclear how the typical high operating temperatures of the systems influence their charge-carrier concentrations. In this work, we use first-principles calculations to examine how lattice vibrations impact electrical conductivity in conventional electrolytes, using BaZrO_{3} as a representative material. Our analysis shows that phonon-induced shifts in the band gap and band edges lead to a dramatic increase in p-type carrier concentrations at temperatures above 600 K, compared to models that neglect temperature effects. Additionally, we reveal the importance of oxygen-ion motion on band-edge positions, which makes valence-band-edge shift dominate the band-gap change. Our study provides a protocol for calculating phonon-induced changes in similar oxides, paving the way for interrogating electrical leakage in electrolytes for high-temperature operation.